2014
DOI: 10.1136/gutjnl-2014-307094
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the usefulness of epigenetic cancer risk prediction by a multicentre prospective cohort study

Abstract: BackgroundEpigenetic alterations accumulate in normal-appearing tissues of patients with cancer, producing an epigenetic field defect. Cross-sectional studies show that the degree of the defect may be associated with risk in some types of cancer, especially cancers associated with chronic inflammation.ObjectiveTo demonstrate, by a multicentre prospective cohort study, that the risk of metachronous gastric cancer after endoscopic resection (ER) can be predicted by assessment of the epigenetic field defect using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(153 citation statements)
references
References 34 publications
7
144
2
Order By: Relevance
“…MGC was defined as a new gastric cancer detected at least 1 year after successful H. pylori eradication and located in an area other than the site of the previous endoscopic resection; this definition was in accordance with the previous study [23].…”
Section: Surveillance Endoscopy and Definition Of Metachronous Gastrimentioning
confidence: 70%
See 3 more Smart Citations
“…MGC was defined as a new gastric cancer detected at least 1 year after successful H. pylori eradication and located in an area other than the site of the previous endoscopic resection; this definition was in accordance with the previous study [23].…”
Section: Surveillance Endoscopy and Definition Of Metachronous Gastrimentioning
confidence: 70%
“…Implementation of third-line and further eradication therapy was at the discretion of the attending physician. To confirm continuous H. pylori negative status, the urea breath test, serum anti-H. pylori antibody test, and the culture method were performed at 3 and 5 years after the patients' enrollment in the previous study [23]. If any of these follow-up examinations revealed positivity for H. pylori, additional eradication was performed.…”
Section: Detection Of Helicobacter Pylori Infection and Its Eradicationmentioning
confidence: 99%
See 2 more Smart Citations
“…The multivariate analysis showed that atrophic type or intestinal metaplasia was the strong independent risk for DNA methylation after H. pylori eradication. Although DNA hypermethylation might be a risk of gastric cancer regardless of H. pylori infection status [6,[19][20][21], in our study, the most important factor of DNA hypermethylation was magnifying NBI and histologic features. This indicates that the methylation change is closely linked to the magnifying NBI and histologic features within the focal points.…”
Section: Discussionmentioning
confidence: 77%